Theories of international relations (realist-liberal) and the future of the international system (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The science of (International Relations) began to crystallize its features, foundations and theories after the end of the World War in an attempt to study the causes of the outbreak of war and find solutions to the outbreak of the World War and the occurrence of major and articulated events in the World Automobile World II system, the Cold War and the disintegration of the Soviet Union, several theories emerged in the field of international relations to explain reality among the most prominent of these are Realism and Liberal theories, in addition to some critical schools such as Marxism and Feminism and Constructivism, and each of these theories represents an extension of a certain historical, philosophical and intellectual legacy, and these theories play the role of criterion and yardstick through which to explain events on the international scene, analyze reality, and predict the future.